2020
DOI: 10.17509/jaz.v3i1.18621
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Bukaan Terhadap Pencahayaan Alami Dan Penghawaan Alami Pada Masjid Al Ahdhar Bekasi

Abstract: The building should be able to provide a comfortable space for users to avoid outside unfavorable climate, so that the activities in it can run optimally. The comfort aspect is one of the important factors in special worship in it. Al-Ahdhar Mosque is a mosque designed by architect Nataneka. This mosque has large openings so that natural lighting and natural ventilation can enter the building. However, it needs to be investigated whether this large opening is enough to influence the lighting conditions and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
9
0
3
Order By: Relevance
“…The optimal WWR value depends on the exact set of many variables during the design process. Therefore, the situation becomes a problem between the need for natural light and the effects of entering the light [16]. One strategy that can be used to utilize natural lighting is to use window openings or the Window Wall Ratio (WWR) (17).…”
Section: Corellation Wwr Between Daylightingmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal WWR value depends on the exact set of many variables during the design process. Therefore, the situation becomes a problem between the need for natural light and the effects of entering the light [16]. One strategy that can be used to utilize natural lighting is to use window openings or the Window Wall Ratio (WWR) (17).…”
Section: Corellation Wwr Between Daylightingmentioning
confidence: 99%
“…North-and west-facing façades in colder climates and a west-facing façade in warmer and drier climates were the most sensitive ones, with a significant increase in energy use when a non-optimal WWR was chosen. [16,14] Each orientation and climate requires a dedicated optimal transparent percentage. However, it has been shown that the optimal WWR range is instead limited across very different climates, especially for some orientations.…”
Section: Grafik 2 Correlation Between Wwr and Natural Lightingmentioning
confidence: 99%
“…A large opening area will affect the level of natural lighting in the room, but at the same time it also includes large amounts of solar heat (Vidiyanti, et al, 2020). Recent research has tried to analyze the correlation of energy efficiency and visual comfort in the room by integrating the study of energy efficiency of the building envelope and natural lighting sustainably (Altan, et al, 2015).…”
Section: Correlation Of Building Thermal Performance With Daylight Pe...mentioning
confidence: 99%
“…Aspek kenyamanan termal membuat aktivitas di dalam bangunan menjadi berhasil dilakukan dengan baik. Ventilasi tidak hanya terkait dengan besaran ukuran saja namun juga terkait dengan peletakan, orientasi dan jenis ventilasinya (Vidiyanti et al, 2020). Selain itu, iklim tropis sangat mempengaruhi tata ruang dan tata letak bangunan dalam sebuah permukiman.…”
Section: Pendahuluanunclassified